Prevention of cases with fungus is a guarantee of Health - Qoziraximova Nargiza Qodirjonovna; Izzatullayeva Dilfuza Ne'matovna; Odilbekova Mahzuna Murodjon qizi (Academia One Publishing, 2023)
This article explores the significance of preventing cases of Fungus as a crucial aspect of ensuring overall health and well-being. Fungus, a relatively new health concern, demands attention to mitigate its impact. Through an analysis of existing literature, this article delves into effective prevention methods, highlighting the role of lifestyle choices and public health initiatives. The results section presents key findings, and the discussion section explores implications, challenges, and potential solutions. In conclusion, the article emphasizes the importance of proactive measures to guarantee health and offers suggestions for individuals and public health efforts.
Keywords: Fungus; health prevention